2018
DOI: 10.1080/15378020.2018.1546076
|View full text |Cite
|
Sign up to set email alerts
|

Loyalty toward online food delivery service: the role of e-service quality and food quality

Abstract: This study assesses the direct influence of food quality and e-service quality on customer loyalty towards OFD service and its indirect influence through the mediation of customer satisfaction and perceived value. This study uses a survey of 405 OFD service customers from Bandung, Indonesia. By applying variance-based partial least squares to evaluate the proposed model, this study confirms the direct effect of food quality on online loyalty, but not e-service quality. Further, this study discloses the partial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
301
5
40

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(379 citation statements)
references
References 38 publications
33
301
5
40
Order By: Relevance
“…Previous research into online food delivery services is limited. A narrative review identified business reports stating that convenience and choice of food outlet were potential drivers of online food delivery service use, supporting findings from Malaysia and Indonesia [16,23]. A further study investigated the availability of food outlets through an online food delivery service in one city in each of Australia, the Netherlands, and the USA [24].…”
Section: Introductionmentioning
confidence: 78%
“…Previous research into online food delivery services is limited. A narrative review identified business reports stating that convenience and choice of food outlet were potential drivers of online food delivery service use, supporting findings from Malaysia and Indonesia [16,23]. A further study investigated the availability of food outlets through an online food delivery service in one city in each of Australia, the Netherlands, and the USA [24].…”
Section: Introductionmentioning
confidence: 78%
“…With the increased availability of innovative technologies, there is an urgent need to understand how food service operations could benefit from new technologies and enhance their effectiveness in various business areas, such as marketing, recruitment, customer service, and overall operations (Di Pietro et al, 2012). Several studies suggest that not only food itself, but also e-service represents a relevant component for restaurants, especially for those offering OFD services (Suhartanto et al, 2019). Recent technological developments have enabled artificial intelligence (AI) to provide e-service agents that help companies improve services and build positive customer relationships (Chung et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The existing body of research is rich with studies on the quality of interpersonal services (e.g. Prentice & Kadan, 2019 ; Scheidt & Chung, 2019 ; Suhartanto et al, 2019 ), with a lack of research on customer responses to automated services, specifically AI-enabled services ( Prentice, Dominique Lopes, & Wang, 2020 ). As AI- enabled services tend to be built around self-service technologies, service quality in the context of AI-enabled services is likely to differ significantly from interpersonal services.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The conceptualisation of service quality in different contexts is well understood (e.g. Parasuraman, Zeithaml, & Berry, 1994 ; Collier & Bienstock, 2006 ; Scheidt & Chung, 2019 ; Suhartanto, Helmi Ali, Tan, Sjahroeddin, & Kusdibyo, 2019 ). What is less understood is the potential for AI-based shopping experiences to provoke shifts in how consumers (a) perceive service quality, (b) adjust their commitment to the relationship, and (c) evaluate their overall AI- enabled experience.…”
Section: Introductionmentioning
confidence: 99%